Encouraging the Implementation of Digitalization Through Micro, Small and Medium-Sized Enterprises (MSME) In Indonesia - Utami, Hapsari Wiji; Istiandari, Debby Nindya (Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2023)
This study aims to determine and analyze the challenges and efforts to implement digitalization in micro, small and medium enterprises in Indonesia. This study uses qualitative descriptive analysis techniques, researchers collect information and secondary data from various sources and research results from previous journals related to the digitization of micro, small, and medium enterprises. From the results of the study, information was obtained that the challenge of micro, small and medium enterprises in implementing digitalization is to return to human resources who have low knowledge about digitalization, low skills, lack of experience, as well as the low interest of micro and small businesses to want to learn information and communication technology, besides that lack of access to supporting facilities and infrastructure is also an obstacle to the implementation of digitalization. Meanwhile, basically the Indonesian Government has taken quite a lot of steps to optimize the productivity of micro, small and medium enterprises in the midst of the rapid development of digital technology. Based on this, the author suggests that the Government of Indonesia more intensively optimize the equitable implementation of digitalization in micro, small and medium enterprises in Indonesia which is also followed by increasing digital literacy for micro, small and medium enterprises. In addition, the command can also support the acceleration of digitalization of micro, small and medium enterprises through the development of supporting facilities and infrastructure related to information and communication technology.